2014
DOI: 10.1007/s10549-014-3109-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of solid palpable masses assessed as BI-RADS 3 or 4A: a retrospective review

Abstract: The purpose of this study was to evaluate the outcomes and cancer rate in solid palpable masses with benign features assessed as BI-RADS 3 or 4A. This study was Institutional Review Board approved. Mammography and breast ultrasound reports in our Radiology Information System were searched for solid, palpable masses with benign features described from 1/1/2000 to 12/31/2009, and retrospectively reviewed. Those masses prospectively assessed as BI-RADS 3 or 4A, or suggestive of a fibroadenoma or other benign path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
2
13
1
Order By: Relevance
“…Our nomogram of the low-risk group was able to help 95.4% of patients avoid a biopsy, based only on a few essential factors, i.e., family history of breast cancer, US imaging features, and calcifications on MG imaging. A study by Patterson et al showed that breast cancer risk was higher in women aged >40 with BI-RADS 4A US lesions; however, this was not observed in our study (20). In the multivariate analyses, 6 variables were found to be independent predictors for malignant diagnosis, including a family history of breast cancer, US imaging features (i.e., margin, shape, orientation, lymph nodes), and calcifications on MG imaging.…”
Section: Discussioncontrasting
confidence: 89%
“…Our nomogram of the low-risk group was able to help 95.4% of patients avoid a biopsy, based only on a few essential factors, i.e., family history of breast cancer, US imaging features, and calcifications on MG imaging. A study by Patterson et al showed that breast cancer risk was higher in women aged >40 with BI-RADS 4A US lesions; however, this was not observed in our study (20). In the multivariate analyses, 6 variables were found to be independent predictors for malignant diagnosis, including a family history of breast cancer, US imaging features (i.e., margin, shape, orientation, lymph nodes), and calcifications on MG imaging.…”
Section: Discussioncontrasting
confidence: 89%
“…In this age group, biopsy rather than followup is recommended in newly diagnosed breast lesions. This is because increasing age is a risk factor for developing breast cancer, as others have suggested [25,26]. Our data indicate that significantly fewer women with BI-RADS 5 lesions had a positive family history compared to women with BI-RADS 3 lesions.…”
supporting
confidence: 55%
“…These results are comparable to the study done by Patterson et al (2014) which showed no cancer in BIRADS 3 group on biopsy and the lesions showed stability on follow up imaging. The study done by Raza et al, (2008), although did show cancer in the BIRADS 3 masses, the number was very small (0.8%) and all were diagnosed on initial 6-month follow-up examination, also they were less than 1 cm in size and without positive axillary nodes.…”
Section: Discussionsupporting
confidence: 88%